THE RELATION OF POWER IN FILM ‘THE JUDGE’: A CRITICAL DISCOURSE ANALYSIS - Wahyuni, Sri; Setyowati, Yulis; Probowati, Yeni (TELL - US JOURNAL, 2024)
This research explores how discourse, actors, societal structures, power dynamics, and illocutionary acts play significant roles in shaping communication and influencing individuals' beliefs and attitudes. It emphasizes the importance of analyzing language and social interactions to gain a deeper understanding of how power and meaning are constructed and perpetuated in society. The researcher employed the concept of code-switching to interpret the film "The Judge" and derive insights into the dynamics of power within it. Social interaction and language were scrutinized through Communication Discourse Analysis (CDA), with van Dijk's Critical Discourse Analysis serving as the overarching theoretical framework, addressing core aspects such as grammar, metaphor, intonation, social cognition, and societal structures. A descriptive qualitative approach was utilized for data analysis. The film's script was referenced extensively. The researcher focused on the protagonist due to the significance of their remarks in shaping social relations and legal contexts. The investigation uncovered instances of power dynamics, including the manipulation and coercion employed by key figures. These protagonists exploited their authority within the community to dictate agendas.